Gut microbiota induces DNA methylation via SCFAs predisposing obesity-prone individuals to diabetes. (August 2022) - Guo, Wenqian; Zhang, Zengliang; Li, Lingru; Liang, Xue; Wu, Yuqi; Wang, Xiaolu; Ma, Han; Cheng, Jinjun; Zhang, Anqi; Tang, Ping; Wang, Chong-Zhi; Wan, Jin-Yi; et al.
Abstract: Obesity-prone (OP) individuals have a significant predisposition to obesity and diabetes. Previously, we have found that OP individuals, despite being normal in weight and BMI, have already exhibited diabetes-related DNA methylation signatures. However, the underlying mechanisms remain obscure. Here we determined the effects of gut microbiota on DNA methylation and investigated the underlying mechanism from microbial-derived short-chain fatty acids (SCFAs). Diabetes-related DNA methylation loci were screened and validated in a new OP cohort. Moreover, the OP group was revealed to have distinct gut microbiota compositions, and fecal microbiota transplantation (FMT) demonstrated the role of gut microbiota in inducing diabetes-related DNA methylations and glucolipid disorders. UPLC-ESI-MS/MS analysis indicated a significantly lower level of total fecal SCFAs in the OP group. The gut microbiota from OP subjects yielded markedly decreased total SCFAs, while notably enriched propionate. Additionally, propionate was also identified by variable importance in projection (VIP) score as the most symbolic SCFAs of the OP group. Further cellular experiments verified that propionate could induce hypermethylation at locus cg26345888 and subsequently inhibit the expression of the target gene DAB1, which was crucially associated with clinical vitamin D deficiency and thus may affect the development and progression of diabetes. In conclusion, our study revealed that gut microbiota-derived propionate induces specific DNA methylation, thus predisposing OP individuals to diabetes. The findings partially illuminate the mechanisms of diabetes susceptibility in OP populations, implying gut microbiota and SCFAs may serve as promising targets both for clinical treatment and medication development of diabetes. Graphical Abstract: ga1